Evaluating the effects of Lactobacillus plantarum, Bacillus subtilis and mannan-oligosaccharides (MOS) on serum protein and lipid profiles in broiler chicken - T.P. Shamna; Binoj Chacko; Stella Cyriac; G. Simi; G. Radhika; Deepa Jolly (Journal of Veterinary and Animal Sciences, 2025)
This study assessed the influence of dietary supplementation with Lactobacillus plantarum, Bacillus subtilis, mannan-oligosaccharides (MOS) and their combinations on serum lipids and protein profiles and immune organ weights in broiler chicken. A total of 216-day-old Cobb broiler chicks were assigned to six treatment groups with each group comprising three replicates of 12 birds each, ensuring a completely randomised design (CRD): T1 (control), T2 (L. plantarum), T3 (B. subtilis), T4 (MOS), T5 (L. plantarum MOS) and T6 (B. subtilis MOS). Data collected were analysed by one-way ANOVA using SPSS (version 24.0). Significant differences in triglycerides (p 0.04), LDL (p 0.04), and VLDL (p 0.03) levels were observed, with T5 (L. plantarum MOS) and T6 (B. subtilis MOS) groups showing reduced lipid levels compared to other treatments. No significant differences were found in total cholesterol, HDL, total protein, albumin, globulin levels, or the weight of immune organs (bursa and spleen). These results indicate that probiotics and prebiotics combinations may have beneficial effects on lipid metabolism in broilers, while their influence on protein levels and immune organ development is minimal.